A Supply Chain Risk Management for Dadih Product by Pricing Optimization - D. Delfitriani; Taufik Djatna; Ma’ruf Pambudi Nurwantara (SEAS (Sustainable Environment Agricultural Science), 2018)
Risk mitigation by using risk sharing approach is a method to minimize risk on supply chain management. In this case, the pricing optimization is needed to maximize and to balance the profit of each stakeholder on its sphere. This paper focused on Dadih product supply chain risk modelling which has three objectives: (1) to identify, (2) to evaluate the risk of each sphere along Dadih product supply chain, and (3) to build a supply chain risk management model for Dadih product by pricing optimization. The model is started by risk identification which showed that there were 52 risks along the whole chain. Then these risks were evaluated by using risk index measurement which showed that the dairy farmer sphere has the highest risk proportion on the whole chain. Finally, the optimum prices were obtained by using risk sharing model which is generated from the result of risk evaluation and the result of stakeholder efficiency measurement by using DEA method. We also found that the prices fluctuation among the DMU became smoothly after the optimization which occurred as a result of risk distribution along the chain.